ANALISIS TREND PENGANGGURAN PASCA COVID-19 - Fitri Handayani; Noviar, Helmi (Fakultas Ekonomi Universitas Almuslim Bireuen, 2022)
This study aims to analyze the trend of unemployment and work in Aceh Province after the Covid-19 pandemic. The Covid-19 pandemic has led to a higher unemployment rate. This study uses secondary data, namely time series data using the least squares analysis method or forecasting method. The results of this study indicate that unemployment in Aceh Province for the next three years will decrease, while for work there has been an increase in workers. This has a positive effect on unemployment and employment rates in Aceh Province. With this forecasting method, the government should make it to the appropriate investment policies to reduce unemployment.